Implementation Of The Settlement Of The Case Restorative Justice In Fights By Children Because The Effect Of Liquor (Case Study In The Polres Kudus) - Hadi Noor Cahyo; Maryanto Maryanto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Settling disputes fight by children because of the influence of liquor based on the Law applicable Relative authority possessed by police, then in handling ABH, the police can make or use the authority the discretion of the need to continue the legal process. Restorative Justice approach used in settling disputes fight by children because of the influence of liquor in the best interest of children of law enforcement officers are already implementing Discretion (Police Authority) and Diversion Restorative Justice approach based on each brat who committed the crime. According to Act No. 11 Of 2012 on Child Criminal Justice System, Restorative Justice approach is highly required as for the approach made through Diversion is applied at every stage of the proceedings. With the Discretion (Police Authority) and Diversion at every stage of the proceedings under the Child Criminal Justice System provides a great opportunity to keep the child out of the judicial process that is not needed in order to maintain mental, moral, and future of the child.Obstacles and solutions for settling disputes fight by children because of the influence of liquor through the mechanism of Restorative Justice Approaches Related to the competence of the investigators in the field of legal knowledge, laws and regulations, the criminal justice system and the technical skills and tactical investigation is still not optimal. This happens because not all personnel functions reskrim follow vocational education and skills of detectives technical functions supporting for example the ability to use information technology in the disclosure of a criminal case. Including in this case the lack of a comprehensive understanding of the principles of restorative justice.Keywords: Restorative Justice, Kids Fighting, Liquor.